Cell wall compositional changes during incubation of plant roots measured by mid-infrared diffuse reflectance spectroscopy and fiber analysis - White, Kathryn E.; Reeves, James B.; Coale, Frank J. (Geoderma, 2016)
Plant roots, particularly the constituents of root cell walls (hemicellulose, cellulose and lignin) are important contributors to soil organic matter. Little is known about the cell wall composition of many important crop species or compositional changes as roots decay. The objectives of this study were to quantify changes in root cell wall composition during a four week laboratory incubation by forage fiber analysis and characterize those changes using diffuse reflectance infrared fourier transform spectroscopy (DRIFTS). The roots of six important crop, forage and native grass species were incubated at 25°C and sampled weekly. Alfalfa lost 78% of initial mass over four weeks, while the remaining species lost between 19% and 38%. For all species the majority of this loss occurred during Week 1, and only alfalfa mass loss was significant (P<0.05) each week. The trends observed for whole root decomposition were paralleled by the decomposability of root cell walls. Significant changes in hemicellulose, cellulose and lignin concentrations over time were only observed in alfalfa roots. Significant changes in decomposability of these constituents was likewise only observed in alfalfa, with cellulose the most decomposable fraction, followed by hemicellulose and lignin. Analysis by DRIFTS supported the fiber analysis results and revealed important changes in root cell wall composition. The disappearance of peaks due to starch in the perennial alfalfa and switchgrass roots following Week 1 helped to explain the greater initial mass loss in both of these species relative to the roots of the annuals. The spectral data also illustrated the resistance of alfalfa lignin to decomposition, the preservation of carbonyl compounds and the degradation of readily decomposed proteins. Finally, changes potentially indicative of wax compound preservation were found in the DRIFTS spectra of alfalfa even though the amount of wax was too small to quantify by fiber analysis. This research study reveals differences in the rate at which crop roots decompose and important changes that can occur in readily decomposable roots over relatively short time scales. These results provide valuable information contributing to the understanding and prediction of short term soil organic matter dynamics which will help to predict possible impact of management changes or soil disturbance on soil health and productivity as well as long term organic C stabilization and the potential for C sequestration. •Quantified and characterized changes in plant root cell walls during decomposition•Only alfalfa roots lost significant mass during each of four week incubation.•Significant changes in alfalfa root cell wall constituent decomposability were measured.•Infrared spectra revealed important changes in root cell wall composition.